2023
DOI: 10.3390/foods12081623
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Self-Assembly of Core-Shell Nanoparticles within Fibers by Coaxial Electrospinning for Intestine-Targeted Delivery of Curcumin

Abstract: Nanotechniques for curcumin (Cur) encapsulation provided a potential capability to avoid limitations and improve biological activities in food and pharmaceutics. Different from multi-step encapsulation systems, in this study, zein–curcumin (Z–Cur) core-shell nanoparticles could be self-assembled within Eudragit S100 (ES100) fibers through one-pot coaxial electrospinning with Cur at an encapsulation efficiency (EE) of 96% for ES100–zein–Cur (ES100–Z–Cur) and EE of 67% for self-assembled Z–Cur. The resulting str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…This indicated that the ES100–CUR fibers improved the thermal stability of the EPO–RTV fibers in the form of bifibers. These findings align with previous research results and demonstrate the thermal decomposition behavior and thermal stability of the studied materials as characterized by TGA analysis. , …”
Section: Resultssupporting
confidence: 92%
“…This indicated that the ES100–CUR fibers improved the thermal stability of the EPO–RTV fibers in the form of bifibers. These findings align with previous research results and demonstrate the thermal decomposition behavior and thermal stability of the studied materials as characterized by TGA analysis. , …”
Section: Resultssupporting
confidence: 92%
“…When combined with electrospinning nanotechnology, pH-sensitive materials offer an effective targeted drug delivery system that addresses issues such as nonspecific tissue distribution and facilitates efficient drug therapy. Colon-targeted drug delivery is a typical pH-sensitive drug delivery system, which overcomes the pH changes in the gastrointestinal tract to deliver drugs effectively (Hou et al, 2023). pH-sensitive polymers exhibited limited solubility in acidic environments, while they can dissolve under neutral or alkaline conditions.…”
Section: Colonmentioning
confidence: 99%
“…Zein, as a plant-derived protein, has unique hydrophobic and hydrophilic regions that enable it to self-assemble into stable nanoparticles, which not only provides an ideal carrier for drug delivery systems but also opens up new avenues for the development of green, sustainable nanomaterials [ 10 ]. At present, the research on zein nanoparticles has been gradually transitioning from basic theoretical exploration to the practical application stage, including optimizing preparation processes, regulating hydrophilic and hydrophobic, improving stability and enhancing targeting [ 11 , 12 , 13 ]. However, there are still issues with how to accurately control the size and enhance the preparation efficiency of zein nanoparticles and dynamically adjust their hydrophilic and hydrophobic interface characteristics.…”
Section: Introductionmentioning
confidence: 99%